Barriers and Facilitators to Accessing Health Services for People Without Documentation Status in an Anti-Immigrant Era: A Socioecological Model (Mary Ann Liebert, 2021)
Purpose: This qualitative study explores the barriers and facilitators to health care from the perspective of providers who care for patients without documentation status in the San Francisco Bay Area. Methods: Twenty-four direct providers were interviewed using semi-structured in-depth interviews. Participants included health care providers and community-based organization leaders. Interviews were independently coded using grounded theory analysis. The socioecological framework was used to develop the interview guide, analyze findings, and guide the discussion. Results: Participants identified fear as a barrier that transcended multiple levels of influence. At the public policy level, national policies, such as public charge and anti-immigration rhetoric, limited access to services. Local expansion of health care coverage, such as Healthy San Francisco, facilitated access to care. At the organizational level, law enforcement presence generated fear. This was countered by a welcoming environment, described as culturally concordant clinical sites, representation of the community in the provider pool, and resources to address social needs. Individual-level fear, rooted in trauma and economic insecurity, was eased by trauma-informed care and health navigators. Community engagement and sustained partnerships built trust and credibility to transcend the fear that hindered access to care. Conclusion: In a region with expansive policies for improved health care access, barriers are rooted in fear and span individual, organizational, and public policy levels of access to care. Richer community engagement may lessen the national and systemic barriers that this vulnerable population continues to face. Developing an understanding of this topic improves health care providers' ability to meet the needs of this growing and vulnerable population.